Visibility of early gastric cancer in texture and color enhancement imaging. Issue 1 (24th August 2021) - Abe, Seiichiro; Yamazaki, Takayuki; Hisada, Izumi Tanimoto; Makiguchi, Mai Ego; Yoshinaga, Shigetaka; Sato, Tomoya; Nonaka, Satoru; Suzuki, Haruhisa; Oda, Ichiro; Saito, Yutaka
Abstract: Objective: There are little data regarding the efficacy of texture and color enhancement imaging (TXI) for early gastric cancer (EGC) diagnosis. This study aimed to compare the color difference and visibility of EGC between white light imaging (WLI) and TXI. Methods: This study included 20 EGCs of 18 patients undergoing endoscopic submucosal dissection. Still images of EGC in WLI, TXI mode 1 (with color enhancement), and TXI mode 2 (without color enhancement), which were consistent in distance, angle, and air insufflation, were constructed by computer simulation. The center of the lesion, eight equal peripheral points 5 mm outside the lesion, and eight inner points two‐thirds of the distance from peripheral points to the EGC lesion center were annotated. Mean color differences (ΔE) of the area between peripheral and inner points per lesion in WLI, TXI mode 1, and TXI mode 2 were analyzed. In addition, four endoscopists independently scored the visibility of EGC images of TXI mode 1 and 2 compared with WLI. Results: Clinicopathological characteristics were as follows: 0‐IIa/0‐IIb/0‐IIc/0‐IIa+IIc = 6/1/11/2, reddish/pale = 10/10, differentiated/undifferentiated = 18/2, median tumor size = 13.5 mm. Mean ΔE ± SD = WLI/TXI mode1/TXI mode2 = 10.3 ± 4.7, 15.5 ± 7.8, and 12.7 ± 6.1, respectively. Mean ΔE was significantly higher in TXI mode 1 than in WLI. Visibility (improved/no change/decreased) was 7/13/0 and 4/16/0 in TXI mode 1 and 2, respectively. The visibility was significantly more commonly improved in the macroscopic type 0‐IIc or 0‐IIb than in 0‐IIa or IIa+IIc in TXI mode 1. Conclusions: TXI could improve the visibility of EGC compared with WLI.